AB0627 Physical activity by self-reported physical activity and lupus nephritis in patients with systemic lupus erythematosus. (12th June 2018) - Kim, S.-K.; Choe, J.-Y.; Park, S.-H.; Lee, H.
Abstract : Background: Physical activity is found to be associated with clinical status such as disease activity, organ damage, disability, fatigue, and quality of life in systemic lupus erythematosus (SLE). Objectives: The aim of this study was to identify the association between physical activity and disease activity and organ damage in patients with SLE. Methods: A total of 415 patients with SLE were consecutively enrolled from KORean lupus Network (KORNET) registry. This registry assessed clinical features, disease activity Systemic Lupus Erythematosus Disease Activity Index 2000 [SLEDAI-2K]), and disease damage (Systemic Lupus International Collaborating Clinics/American College of Rheumatology [SLICC/ACR] damage index [SDI]) at the enrollment of study. Self-reported physical activity was measured by International Physical Activity Questionnaire (IPAQ). Statistical analyses were used by Mann-Whitney U test and multivariate logistic regression analysis. Results: There is significant difference of vigour activity between patients with lupus nephritis (n=93) and without lupus nephritis (n=322) (p=0.012), but not moderate and walking activities. In contrast, the differences of each physical activity, walking, moderate, and vigorous intensity, according to SLEDAI-2K and SDI were not found. In addition to high PCS of SF-36 (p=0.006) and SLEDAI-2K (p=0.038), less vigorous physical activity were related with lupus nephritis (p=0.033). However, the risk of CVD was not associated with physical activity of SLE. Conclusions: This study showed that patients with lupus nephritis had less vigorous physical activity. It implicates that SLE-related organ damage might be associated with levels of physical activity. References: [1] Costenbader KH, Wright E, Liang MH, Karlson EW. Cardiac risk factor awareness and management in patients with systemic lupus erythematosus. Arthritis Rheum2004;51:983–8. [2] Katz P, Julian L, Tonner MC, Yazdany J, Trupin L, Yelin E, Criswell LA. Physical activity, obesity, and cognitive impairment among women with systemic lupus erythematosus. Arthritis Care Res (Hoboken)2012;64:502–10. Disclosure of Interest: None declared